Socio-Economic Analysis of Soyabeanutilization in Akure South Local Government Area, Ondo State - J.A. Folayan; J.O. Bifarin (Journal of Basic & Applied Sciences, 2013)
This study was carried out for the purpose of analyzing the socio-economic of soyabean inAkure South Local Government Area of Ondo state with the objective of examining the socio-economic characteristics of the respondents Data were collected from one hundred (100) respondents drawn from five communities using well structured questionnaire. The data were analyzed using frequency distribution, percentages and regression model while gross margin was used to determined the profitability of the utilization operators. The outcome of the study revealed that 76% of the respondents involved in utilization were females, about 82% of the respondents were married and 87% were educated. All 100% of the respondent reported that utilization increase their annual incomes. The gross margin result revealed that N11, 877 accrued to a respondent per month in the study area. The outcome of regression analysis revealed that the level of education, occupation, family size, experience and annual income had positive correlation with quantity of utilization whereas, the negative correlation in the storage, inadequate finance, lack of producing farmers, inadequate enlightenment campaign programme by extension workers were emphasized as the problems confronting the utilization in the area. It is recommended that the government should put in place adequate and efficient credit facility to enhance operational activities, provide regular and continuous enlightenment campaign programme by extension workers to the respondents and assist in the regular provision of adequate storage facilities and power supply for preservation of the products.